Fabrication of a Flexible Micro Temperature Sensor for Micro Reformer Applications - Lee, Chi-Yuan (Molecular Diversity Preservation International (MDPI), 2011)
Micro reformers still face obstacles in minimizing their size, decreasing the concentration of CO, conversion efficiency and the feasibility of integrated fabrication with fuel cells. By using a micro temperature sensor fabricated on a stainless steel-based micro reformer, this work attempts to measure the inner temperature and increase the conversion efficiency. Micro temperature sensors on a stainless steel substrate are fabricated using micro-electro-mechanical systems (MEMS) and then placed separately inside the micro reformer. Micro temperature sensors are characterized by their higher accuracy and sensitivity than those of a conventional thermocouple. To the best of our knowledge, micro temperature sensors have not been embedded before in micro reformers and commercial products, therefore, this work presents a novel approach to integrating micro temperature sensors in a stainless steel-based micro reformer in order to evaluate inner local temperature distributions and enhance reformer performance.